1997
DOI: 10.2190/c770-awa1-cmqr-ytyv
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Effective Use of Technology in Education: Current Status

Abstract: While the number of computers in the classroom continues to increase and tremendous support for technology integration exists in government, business, and academia, a major discrepancy exists between the level of technology use expected of educators and the actual use and integration of technology in the classroom. This article examines barriers that impede the effective use of technology in education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0
10

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 15 publications
8
100
0
10
Order By: Relevance
“…This study supports the review of several meta-analyses by Fabry and Higgs (1997) and the research by Smerdon, et al (2000), in which they found that some of the major issues in integrating technology into instruction included training, access to technology, and various other barriers to the integration of technology. For both marketing teachers and their students, technology should be used as the basis of an instructional environment that enriches the teaching/learning experience.…”
Section: Recommendations and Implicationssupporting
confidence: 88%
See 2 more Smart Citations
“…This study supports the review of several meta-analyses by Fabry and Higgs (1997) and the research by Smerdon, et al (2000), in which they found that some of the major issues in integrating technology into instruction included training, access to technology, and various other barriers to the integration of technology. For both marketing teachers and their students, technology should be used as the basis of an instructional environment that enriches the teaching/learning experience.…”
Section: Recommendations and Implicationssupporting
confidence: 88%
“…This conclusion does not support the review of meta-analyses conducted by Fabry and Higgs (1997), and the national study conducted by the National Center for Education Statistics (Smerdon et al, 2000), in which they concluded that teachers were encountering barriers in their efforts to integrate technology in instruction. In general, marketing teachers are not experiencing technology anxiety at a level that prevents them from using technology in their instruction.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As argued by Fabry and Higgs (1997), ICT access is no longer a crucial issue in the schools studied. Yet, there still remains a need for policy makers and teachers to realize the important pedagogical values of ICT as a leaning enhancer.…”
Section: Discussionmentioning
confidence: 99%
“…Access to ICT, once identified as one of the major barriers to teachers' use of technology (Fabry & Higgs, 1997;Lehman, 1994), has become a less critical issue. As various kinds of ICT such as computer hardware and software, Internet, digital camcorders and cameras, digital music players, and mobile phones become available and affordable, people from both developed and developing nations now at a certain degree have access to one or more kinds of ICT.…”
Section: Literature Reviewmentioning
confidence: 99%